Tests and proofs : 12th International Conference, TAP 2018, held as part of STAF 2018, Toulouse, France, June 27-29, 2018, Proceedings /: 12th International Conference, TAP 2018, held as part of STAF 2018, Toulouse, France, June 27-29, 2018, Proceedings. (2018) - Unknown
No abstract available